Self Management among Diabetes Patients - K.C., Nyamika; Shah, Pammi; Dhami, Kabita; Pokhrel, Khushi; Shah, Nisha Kumari; K.C., Mamta (Journal of Nobel Medical College, 2023)
Background: In the management of diabetes mellitus, the role of self-care has been pivotal. Individuals with diabetes have been shown to make a dramatic impact on the progression and development of disease by participating in their care.This study aimed to assess self-management among diabetes patients. Materials and Methods: Analytical cross-sectional study was conducted among 232 patients with diabetes selected by convenience sampling. Diabetes Self Management Questionnaire-Revised was used to assess self-management among diabetes patients. Data were analyzed using descriptive statistics (frequency, percentage, mean, and standard deviation) and inferential statistics (bivariate logistic regression). Results: Findings of the study revealed that out of 232 respondents, 48.7% had suboptimal diabetes self-management practices. The global score for diabetes self-management was 5.28± 1.34 The mean score for subscale cooperation with the diabetes team was highest i.e., 7.50± 1.94 followed by medication taking subscale (6.94±3.14), physical activity subscale (5.37± 3.09), eating behavior subscale (5.35±1.71) and glucose monitoring subscale (0.83± 2.19) respectively. The results further indicated a significant association between diabetes self-management and religion, type of diabetes medication, glycemic control, and diabetes complications at p<0.05. Conclusion: The present study showed that almost half of the respondents had suboptimal diabetes self-management. Therefore, healthcare providers should further design and implement interventions to improve self-management behavior among diabetes patients